Towards the Perception and Usage of the Metaverse for Businesses in Brazil - Jorge, Lucas Ribeiro; Villela, Nicholas Capone; Braz, Rodrigo Moreira; Mendonça, Diogo Silveira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: The Metaverse is a disruptive technology that is being explored globally by companies. However, there is limited knowledge about its perception and use in Brazil. Problem: There is a knowledge gap regarding how the Metaverse is perceived and utilized by Brazilian companies, especially in terms of business models and internal communication. Proposed Solution: This study aims to better understand the perception and use of the Metaverse in the Brazilian business context. IS Theory: The study addresses the interaction between disruptive Metaverse technology and the business environment, focusing on practical application within the context of Information Systems, which fits to the Diffusion of Innovations Theory. Methodology: A questionnaire survey was developed on the knowledge and use of the Metaverse, distributed through social networks, and an interview was conducted with an expert in the field, yielding 61 respondents. Summary of Results: The research revealed a positive perception of the Metaverse, highlighting its potential to enable new business models and improve internal communication in companies. Contributions and Impact for IS area: The results help clarify how the Metaverse can be utilized in Brazil, assisting companies in directing their investments in the area and overcoming challenges such as training, user collaboration, and information security.